Turbulent kinetic energy climatology for present and future climate conditions over the Iberian Peninsula as obtained from a TKE closure scheme in a regional climate model - Yagüe, Carlos; Sánchez, Enrique; Gaertner, Miguel Angel (Física de la Tierra, 2008)
Two 30-year periods, present (1961-1990) and future (2071-2100) climatic conditions under A2-SRES increased greenhouse gases conditions over mosf of Europe and Northern Africa have been simulated with PROMES regional climate model. This model uses a 1.5 order closure turbulent scheme, providing then turbulent kinetic energy (TKE) as a prognostic variable. The analysis of the obtained TKE at climatic scales provides additional information about climatic change processes than just the surface variables analysis, more commonly used for climate change studies. It also gives an original perspective for numerical modelling of turbulent planetary boundary layer description, typically focused on much smaller time and spatial scales. The analysis is here focused over the Iberian Peninsula, as it shows some aspects of interest when dealing with climatic change studies over Europe: it is one of the regions that is expected to present a higher temperature increase, specially for summer season, and also can suffer an important hydrological stress.